Case Study: Post-Orif Joint Stiffness Following a Distal Third Right Tibial Fracture Managed with Infrared Radiation Therapy and Exercise - Puspita, Wita Hana; Fazrina, Gina; Agustyaningsih, Nugrahaeni; Izzatul Aziz, Faza (Rifa'Institute, 2026)
Fractures of the tibia 1/3 distal dextra after Open Reduction External Fixation (OREF) often cause joint stiffness, pain, oedema, muscle atrophy, as well as limitations in joint range of motion (LGS) and functional activity. The administration of physiotherapy with Infrared Radiation (IRR) modalities and exercise therapy is a non-invasive approach to overcome these complications. This study used a case study method, in a 61-year-old female patient, with the provision of interventions in the form of IRR and exercise therapy such as static contractions, free active exercises, active resistance training, and non-weight bearing (NWB) walking exercises using walkers. After 6 sessions of therapy, compressive pain decreased, motion pain decreased, oedema in the maleolus decreased, LGS eversi-inversion increased and LGS plantar-dorsal flexion increased, knee flexor muscle strength, dorsal flexor ankle, plantar flexor ankle, as well as evertor and invertor ankle increases, the circumference of the right thigh muscle increases, and the value of functional ability increases